Judicial Defence of Constitutionalism in the Assessment of South Africa's International Obligations - Francois Venter (Potchefstroom Electronic Law Journal, 2019)
The (sometimes fragile) balance between South Africa's constitutional obligations to protect and promote human rights in the international arena and the realities of political practice is the focus of this paper. The Constitution provides for solid dualist mechanisms and procedures for parliamentary oversight of the executive's conduct in the governance of international relations, including the conclusion of treaties. There is, however, a congenital constitutional flaw in the oversight instrumentation of the Constitution: the president is endowed with practically unfettered control over cabinet, and through the cabinet and the parliamentary caucus, he has indirect but firm control over parliament. Consequently, parliamentary oversight of international relations is severely challenged, effectively leaving it to the minority parties, civil society and the courts.